Phytochemical study and anti-inflammatory activity of Annona muricata L. (Soursop) from Cuzco - Poma, Elizabeth M. (2011)
To give scientific support to the traditional use of plants, was studied the aqueous extract of dried leaves of Annona muricata L. "Soursop", specie collected in the highlands jungle of Cuzco, which was classified taxonomically in the Natural History Museum of the UNMSM; Annona muricata L. revealed the presence of flavonoids and other metabolites. The aqueous extract was classified as non-toxic according to the method of dose limits for the determination of acute toxicity, result supported with the macroscopic study of organs made at the Faculty of Veterinary Medicine UNMSM. By employing the method of plantar edema induced by λ-carrageenan mouse model, the aqueous extract of Annona muricata L., at concentration of 1,5mg/kg, had significant anti-inflammatory efficacy compared to indomethacin. The statistical analysis was carried out by ANOVA at 95% confidence.